Growth Performance, Nutrient Digestibility and Cost-Efficiency of Broiler Chickens Administered Higher Doses of Yohimbe (Pausinystalia yohimbe) and Larvacide - Obajuluwa, Olusola V.; Akangbe, Eghosa E.; Adedotun, Williams G.; Stanley, Eguaoje A.; Osayande, Unity D.; Atinuke, Sanwo K.; Tokunbo, Egbeyale L.; Olusesan, Fafiolu A. (Syiah Kuala University, 2025)
The use of plant-based additives has helped in the improvement of feed utilization, performance, and poultry welfare. Yohimbe is a botanical additive that could be used to achieve these objectives. A total of 225 broiler chickens were randomly into five (5) treatment groups. The group includes: T1 = Control, T2 = 5mg/kg Larvicide, T3 = 240 mg/kg Yohimbe, T4 = 300mg/kg Yohimbe, T5 = 360mg/kg Yohimbe was further divided into 3 replicates. All replicate groups had 15 chickens each with relatively similar live weights. Feed was served to chickens ad libitum at the starter and finisher phases, while data were collected on intake, growth, and later, feed digestibility. Results showed that chickens served 300mg/kg Yohimbe diet had better digestion of carbohydrates, energy, crude fiber, and livability, while other performance parameters were unaffected. It is therefore concluded that Yohimbe can be included up to 300 mg/kg, above which there was a decline in the growth performance and nutrient digestibility of broiler chickens.